2013
DOI: 10.5755/j01.ss.80.2.4852
|View full text |Cite
|
Sign up to set email alerts
|

What does a City Master Plan Tell about our Safety? Comparative Analysis of Vilnius, Kaunas, and Klaipeda

Abstract: High rates of crime have always been considered a serious threat to city development. Crime and urban development are strongly interconnected, therefore, local development policies cannot be successful without crime prevention strategies. One of the areas where local governments are characterized by quite a high degree of independence is that of urban planning, typically documented in a city master plan. In the light of the topic of safety in the urban space, one of the most notable measures of space evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Therefore, sustainable development can be achieved by improving safety and security, and crime can be reduced by the correct implementation of urban planning and design. The study by Stankevice et al [7] revealed that when green areas and specialized areas are incorporated into the residential areas, we observe less crime. Also, public areas combined with residential and green areas lead to crime reduction.…”
Section: Introductionsupporting
confidence: 47%
“…Therefore, sustainable development can be achieved by improving safety and security, and crime can be reduced by the correct implementation of urban planning and design. The study by Stankevice et al [7] revealed that when green areas and specialized areas are incorporated into the residential areas, we observe less crime. Also, public areas combined with residential and green areas lead to crime reduction.…”
Section: Introductionsupporting
confidence: 47%
“…Therefore, it is important to consider these aspects when planning urban design. For example, Stankevice et al [40] demonstrated that specialised areas and greenery in dense residential areas contribute to crime prevention. However, if these areas are combined with local centres, commercial or industrial areas, they become even more attractive to criminals.…”
Section: Introductionmentioning
confidence: 99%
“…Several research cases have proven that planning of land use contributes to the decrease of crime. The research conducted by Stankevice et al [20] demonstrates that specialized areas, greenery when included into dense residential areas, as well as public lands combined with residential and green areas, contribute to less crime. Another example is that pickpocketing often happens in mixed land use areas, mostly commercial.…”
Section: Introductionmentioning
confidence: 99%